1993
DOI: 10.1007/bf01973675
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase reactivation in organophosphorus poisoned patients depends on the plasma concentrations of the oxime pralidoxime methylsulphate and of the organophosphate

Abstract: We measured in nine patients, poisoned by organophosphorus agents (ethyl parathion, ethyl and methyl parathion, dimethoate, or bromophos), erythrocyte and serum cholinesterase activities, and plasma concentrations of the organophosphorus agent. These patients were treated with pralidoxime methylsulphate (Contrathion), administered as a bolus injection of 4.42 mg.kg-1 followed by a continuous infusion of 2.14 mg.kg-1/h, a dose regimen calculated to obtain the presumed "therapeutic" plasma level of 4 mg.l-1, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 22 publications
0
46
0
2
Order By: Relevance
“…It is reasonable to expect that the concentration of methyl parathion, methyl paraoxon or both must fall below a certain level to allow spontaneous reactivation of cholinesterase to outpace inhibition. Such seems to be the case in humans in whom reactivation of cholinesterase with pralidoxime methylsulfate was dependent upon plasma organophosphate concentration [42]. Dealkylation of the phosphoryl-cholinesterase complex may also occur, resulting in an 'aged' enzyme that does not readily reactivate [3].…”
Section: Discussionmentioning
confidence: 96%
“…It is reasonable to expect that the concentration of methyl parathion, methyl paraoxon or both must fall below a certain level to allow spontaneous reactivation of cholinesterase to outpace inhibition. Such seems to be the case in humans in whom reactivation of cholinesterase with pralidoxime methylsulfate was dependent upon plasma organophosphate concentration [42]. Dealkylation of the phosphoryl-cholinesterase complex may also occur, resulting in an 'aged' enzyme that does not readily reactivate [3].…”
Section: Discussionmentioning
confidence: 96%
“…82 Nine patients intoxicated with organophosphorus insecticides were treated with PAM-2 methylsulphate (Contrathion) using a dose of 4.42 mg/kg as a bolus injection followed by continuous infusion 2.14 mg/kg/h. 106 In patients with ethylparathion and methylparathion poisonings, enzyme reactivation could be obtained in some at oxime concentrations as low as 2.88 mg/L. In others, however, oxime concentration as high as 14.6 mg/L were ineffective.…”
Section: Mechanism Of Action Of Pyridinium Oximesmentioning
confidence: 99%
“…Bowever, the fact that no metabolites were detected is not a sure indication that they are not produced. In mammals, it has been shown that in plasma, aetive oxygen analogues are present at levels 30-100 times below parent compound concentrations (Willems et al 1993). Because of the detection limit in this study of 0.5 ng, potentially existing metabolites would have been detected only if they were present at levels 25 times below parent compound concentrations.…”
Section: Discussionmentioning
confidence: 99%